2018
DOI: 10.1103/physreve.97.012402
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic instability in the hook-flagellum system that triggers bacterial flicks

Abstract: Dynamical bending, buckling, and polymorphic transformations of the flagellum are known to affect bacterial motility, but run-reverse-flick motility of monotrichous bacteria also involves the even more flexible hook connecting the flagellum to its rotary motor. Although flick initiation has been hypothesized to involve either static Euler buckling or dynamic bending of the hook, the precise mechanism of flick initiation remains unknown. Here, we find that flicks initiate via a dynamic instability requiring fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…For hydrodynamic signals at high enough frequencies, such as those due to the beating of swimming appendages, the unsteady Stokes equations must be used to calculate the setal bending flows, which will be attenuated by unsteady effects at ranges larger than the viscous dissipation length. Last, our model used Euler beam theory, applicable for small setal deformations, but for larger deflections could be improved by using Kirchhoff rod theories coupled to hydrodynamics (Jabbarzadeh and Fu ).…”
Section: Resultsmentioning
confidence: 99%
“…For hydrodynamic signals at high enough frequencies, such as those due to the beating of swimming appendages, the unsteady Stokes equations must be used to calculate the setal bending flows, which will be attenuated by unsteady effects at ranges larger than the viscous dissipation length. Last, our model used Euler beam theory, applicable for small setal deformations, but for larger deflections could be improved by using Kirchhoff rod theories coupled to hydrodynamics (Jabbarzadeh and Fu ).…”
Section: Resultsmentioning
confidence: 99%
“…Our study shows that an assembly of the flagellar filament by one or two different flagellins affects its mechanistic properties, which has significant consequences for several aspects of flagellar function in different environments. Directional changes of many monopolarly flagellated bacteria are mediated by combined bending of flagellar filament and hook, the structure which joins filament and motor, during the typical run-reverse-flick movement 25,3335 . Thus, the proximal FlaA segment in S. putrefaciens likely has a positive effect on robust directional changes at high and fast swimming at normal viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we assume a constant motor torque applied towards the normal to the cell-body surface, (Shum & Gaffney 2012; Shimogonya et al. 2015; Jabbarzadeh & Fu 2018).…”
Section: Bacterial Hydrodynamicsmentioning
confidence: 99%
“…Compared with the flagellar filament consisting of helical polymers, the short flagellar hook ( in length) is a flexible structure so that it acts like a universal joint, and can be buckled during the swimming motion (Son, Guasto & Stocker 2013), generating a rich diversity of bacterial behaviours (Shum & Gaffney 2012; Nguyen & Graham 2017, 2018; Jabbarzadeh & Fu 2018). Riley, Das & Lauga (2018) considered the hook elasticity for peritrichous bacteria and numerically demonstrated that the elastohydrodynamic instability enables their swimming.…”
Section: Introductionmentioning
confidence: 99%